Gauge‐Induced Floquet Topological States in Photonic Waveguides. Issue 8 (29th June 2021) - Song, Wange; Chen, Yuxin; Li, Hanmeng; Gao, Shenglun; Wu, Shengjie; Chen, Chen; Zhu, Shining; Li, Tao
Abstract: Tremendous efforts are devoted to the research of exotic photonic topological states, in which Floquet systems suggest new engineered topological phases and provide a powerful tool to manipulate the optical fields. Here, a gauge‐induced topological state localized at the interface between two gauge‐shifted Floquet photonic lattices with the same topological order is demonstrated. The quasienergy band structures reveal that these interface modes belong to the Floquet π modes, which are further found to enable an asymmetric topological transport of this interface mode thanks to the flexible control of the Floquet gauge. The intriguing propagations of the gauge‐induced topological states are experimentally verified in a silicon waveguides platform at near‐infrared wavelengths, which show broadband working wavelengths and robustness against the structural fluctuations. This work provides a new route in manipulating optical topological modes by Floquet engineering and inspires more possibilities in photonics integrations. Abstract : The gauge‐induced topological state localized at the interface between two gauge‐shifted Floquet photonic lattices with the same topological order, which are further found to enable an asymmetric topological transport with broadband working wavelengths and robustness against the structural fluctuations, is demonstrated. The results will open a new avenue in manipulating optical topological modes and in assembling on‐chip topological optical devices.